2007
DOI: 10.1111/j.1399-3062.2007.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of Staphylococcus schleiferi subspecies coagulans endocarditis and metastatic infection in an immune compromised host

Abstract: Staphylococcus schleiferi subspecies coagulans is a relatively recently described organism with limited human pathogenicity. Described case reports of infection are primarily limited to canine external otitis with only one reported case of human involvement, localized to a surgical wound infection. Similarities in phenotypic and microbiological characteristics between S. schleiferi subsp. coagulans and S. aureus have resulted in frequent mistakes using common methods of identification. We describe the first ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…This pathogen expresses a clumping factor, as does S. lugdunensis, and it also displays betahemolysin activity that may be responsible for its erroneous identification as S. aureus in the routine laboratory setting (37,40). Clinical reports that describe infections with this pathogen remain scarce, although they appear unusual in their presentation and severity for a CoNS-mediated infection (40,41). The production of a fibrinogen affinity factor might be involved in colonization of the vascular endothelium, one of the primary events in the pathogenesis of infective endocarditis, and its implication has been reported in experimental models of endocarditis (42).…”
Section: Discussionmentioning
confidence: 99%
“…This pathogen expresses a clumping factor, as does S. lugdunensis, and it also displays betahemolysin activity that may be responsible for its erroneous identification as S. aureus in the routine laboratory setting (37,40). Clinical reports that describe infections with this pathogen remain scarce, although they appear unusual in their presentation and severity for a CoNS-mediated infection (40,41). The production of a fibrinogen affinity factor might be involved in colonization of the vascular endothelium, one of the primary events in the pathogenesis of infective endocarditis, and its implication has been reported in experimental models of endocarditis (42).…”
Section: Discussionmentioning
confidence: 99%
“…Various human cases have been described including wound infection, prosthetic infections, and bacteremia (Celard et al, 1997; Da Costa et al, 1998; Freney et al, 1988; Hernandez et al, 2001; Igimi et al, 1990; Kumar et al, 2007; Latorre et al, 1993; Vandenesch et al, 1994). A review of 28 cases in the literature in 2001, reported that all isolates were coagulase negative: 50% of cultures were from wound infections, 19.4% were found in blood cultures, 13.8% from catheter tips, 8.3% from ear exudates, and 5.5% from cerebrospinal fluid.…”
Section: Case Reportmentioning
confidence: 99%
“…However, the subspecies coagulans , which was first described in 1990 from infections of dogs with otitis externa, is truly coagulase positive as it can clot plasma even in the presence of such inhibitors (Igimi et al, 1990; Vandenesch et al, 1994). The first human case of S. schleiferi subspecies coagulans was described in 1994 in a patient with a surgical wound infection of the finger (Kumar et al, 2007; Vandenesch et al, 1994). A second human case, reported in 2007, described a 58 year old male liver transplant recipient who developed S. schleiferi aortic valve endocarditis with multiple other sites involved including blood, ascitic fluid, synovial fluid, and evidence of paravertebral abscess on MRI (Kumar et al, 2007).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Human infection with subsp. coagulans was reported three times in the literature, with isolates from surgical wound infection [8], blood, ascitic fluid, synovial fluid [9], and a left ventricular assist device [10].…”
mentioning
confidence: 99%